The Federal Law of Education in Argentina: Its Application in the Province of Buenos Aires La Ley Federal de Educación en la Argentina:Su Aplicación en la Provincia de Buenos Aires - María Fernanda Arias (Arizona State University, 2005)
The present work seeks to analyze the results of the educational reform of the secondary school system in Argentina initiated by the Ley Federal de Educación in 1993. This article has chosen Greater Buenos Aires, the biggest conurbation in the country, as a "case study." The methodology used is based on quantitative and qualitative surveys administered to the top authorities of state and private schools in the area. We conclude that the reactions toward the reform are, in general, negative. Furthermore, there are no differences in attitudes between private and state schools. Both of them agree that the worst effect is the leveling down of the quality of education. In other words, the main cause of disagreement is mostly pedagogic. En el marco de la "reforma educativa" de la enseñanza media impuesta en la Argentina a partir de la Ley Federal de Educación (1993), se intenta describir los efectos que tuvo esta reforma en el ámbito del conurbano porteño de la provincia de Buenos Aires. Por esta razón, se utilizaron encuestas cuantitativas y cualitativas realizadas a las autoridades de establecimientos educativos públicos y privados del nivel medio, actualmente, Polimodal. En términos generales, la reacción frente a la transformación del sistema educativo en el ámbito analizado se percibe negativa. Además, en las respuestas dadas por las autoridades encuestadas, no se advierten diferencias notables. En todas se subraya la transformación en detrimento de la calidad educativa, lo que lleva a concluir que las razones del rechazo general obedecen principalmente a fundamentaciones de tipo pedagógicas.